Theoretical issues of Ukrainian culture and music art - (:unkn) unknown (My University, 2022)
The collective monograph of researchers and teachers examines the basics of theory and basic methods of cultural issues and musical art of Ukraine in various areas of training future professionals.
монографія
Keywords: musical art; Ukrainian culture